Early experiences: Building up the tools to face the challenges of adult life. Issue 8 (2nd July 2014) - Branchi, Igor; Cirulli, Francesca; Sullivan, Regina M.
ABSTRACT A supportive early environment can strengthen the developing individual and build the foundation for a lifelong health. By contrast, severe stress can alter brain architecture and lead to increased susceptibility for psychopathology. There is a growing emphasis on setting up models that recapitulate the complexity of the perinatal environment, particularly the social experiences, on developmental trajectories. Special attention is paid, on the one hand, to the role of the mother in programming the behavioral, neuroendocrine and metabolic development of the offspring and, on the other, to the relevance of the social interactions with mother and peers in building up the adult individual. Overall, these studies confirm the strong and complex influence of the early ecological niche on adult brain function and behavior and illustrate how a comparative approach provides an important contribution to unravel the mechanisms underlying increased risk for mental illness in a translational perspective. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1661–1674, 2014.